Mathematics
dsgonzalez10116
4

let a=x^2+4. rewrite the following equation in terms of a. (x^2+4)^2+32=12x^2+48

+0
(1) Answers
Kip

we need to factorize each of the terms of the original equation and then substitute the value of a, lets try it: (x^2+4)^2 + 32 = 12x^2 + 48 (x^2+4)^2 + 32 = 12(x^2 + 4) we now substitute a=x^2+4: a^2 + 32 = 12(a) so we have: a^2 -12a + 32 = 0 we can factorize that square trinomial as well if we find two numbers that  added give -12 and multiplied 32: (a - 8)(a - 4) = 0 So the solutions of the equation are a = 8 and a = 4

Add answer